A LINGUAGEM MUSICAL E AS PRÁTICAS MÚSICO-EDUCATIVAS PARA O DESENVOLVIMENTO DE HABILIDADES NA EDUCAÇÃO INFANTIL: um estudo na Unidade de Educação Básica Bernardina Spíndola - CASTRO, Kátia Regina dos Santos (2020)
The research deals with the musical language and the music-educational practices for the development of abilities in the kindergarten. Its general objective was to propose the use of musical language through music-educational practices aimed at the acquisition of skills and learning and the construction of a notebook of music- educational practice activities in e-book format. The research text was organized into eight sections, including the Introduction and the Final Considerations. The study begins by discussing a brief history of childhood and early childhood education in Brazil. We then discuss the continuing education of preschool teachers, and then the musical language and music-educational practices for skills development. In the first three sections we rely on authors such as Gobbi (2010), Lino (2007), Brito (2003), Ariès (1978), Barbieri (2012), Abuchaim (2018), Bellochio (2014), Dias (2012), Duarte Jr. (2010), Kuhlmann Jr (1998), Rosemberg (2008), Rinaldi (2012), Oliveira (2008), Oliveira-Formosinho; Kishimoto (2002), and in official MEC and normative documents such as LDB (1996), RCNEI (1998), DCNEI (2009), CF (1988). The methodology of approach of the research was qualitative, and of procedure we used the research with bibliographic, participant and cartographic approach, having as main theoretical contributions Gil (2017), Boccato (2006), Bogdan and Biklen (1994), Thiollent (1985), Prodanov and Freitas (2013), Deleuze And Guattari (1995), Kastrup; Passos; Escóssia (2009), Kastrup; Passos; Tedesco (2016). Production instruments and data collection: texts, photographs, semi-structured interviews, songs, images, participating observations, field diary. For data analysis and interpretation, we used interview transcripts, teachers' and children's reports, field notes, and response charts. In the sixth section we talk about the intervention at the UEB Bernardina Spíndola with the teachers and young children and in the seventh section we describe what was the basis of our final product. We conclude that the data revealed that throughout the research and intervention that non-music teachers acquired skills and reframed their practices understanding that musicalization occurs through playfulness and in children it was possible to observe that they acquired musical knowledge, skills expressed at each stage. activity performed. We finalize the research with the final product materialized in the activity book of music-educational practices as support for the teachers.